The Effect Self-Efficacy On Economic Problem-Solving Student : Metacognitive Mediation - Diyah Samrotul Fitri; Albrian Fiky Prakoso; Arina Salsabilla Haq (International Journal of Emerging Research and Review, 2023)
Objective: This study aims to determine the effect of self-efficacy directly and indirectly (through metacognition) on students' economic problem-solving. The sample in this study were X-grade students of Surabaya State High School 17 as many as 143 students. Method: Measurement of metacognitive ability includes metacognitive knowledge and metacognitive regulation. Measurement of students' economic problem-solving skills using economic material tests. Self-efficacy measurement includes magnitude, strength, and generality. Data collection using questionnaires and test questions. The data analysis technique used in this study was SEM-PLS analysis with the Warp-PLS approach. Results: The results of this study indicate that the effect of self-efficacy has a very significant effect on students' metacognitive abilities of 0.624 with p < 0.001. and the results of the analysis of the effect of metacognition on economic problem solving amounted to 0.336 and the indirect effect is from self-efficacy through metacognitive mediation and then to economic problem solving which is 0.209. then the total effect of the effect of self-efficacy on economic problem solving directly or indirectly was x 100% = 15,6%. Novelty: The use of variable Economic problem solving is a novelty found in the search process using the Vosviewer application.